Association of Menopausal Hormone Therapy With Breast Cancer Incidence and Mortality During Long-term Follow-up of the Women's Health Initiative Randomized Clinical Trials. Issue 12 (December 2020) - Chlebowski, Rowan T.; Anderson, Garnet L.; Aragaki, Aaron K.; Manson, JoAnn E.; Stefanick, Marcia L.; Pan, Kathy; Barrington, Wendy; Kuller, Lewis H.; Simon, Michael S.; Lane, Dorothy; Johnson, Karen C.; Rohan, Thomas E.; et al.
Abstract : (Abstracted from JAMA 2020;324:369–380) Hormone therapy (HT) for menopausal symptoms and its risk-to-benefit ratio have been a controversial topic within the scientific community for several decades. The complicated benefits and potential adverse events associated with menopausal HT were first reported in 2002 by the Women's Health Initiative (WHI).